SOCIAL MEDIA-BASED DIGITAL MARKETING TRAINING FOR TOURISM AWARENESS GROUPS (POKDARWIS) TO ENHANCE TOURIST VISITATIONS IN NAGARI SISAWAH - Meri Rahmania; Nefi Sulkaisi; Wati Wati; Desi Areva (Universitas PGRI Sumatera Barat, 2026)
Nagari Sisawah possesses significant potential for the development of nature, cultural, and eco-tourism. However, limited knowledge and skills regarding digital marketing strategies, creative content creation, and social media management have hindered optimal destination promotion, resulting in low visibility within the digital landscape. This community service initiative aims to enhance the capacity of the Nagari Sisawah Tourism Awareness Group (Pokdarwis) in implementing social media-based digital marketing strategies to boost the destination's appeal and increase tourist visits. The implementation methods included outreach sessions, training workshops, hands-on practice, and ongoing guidance in social media management. The material covered fundamental digital marketing concepts, social media platform utilization, creative content creation techniques, promotional photography and videography, content calendar planning, and performance evaluation using engagement and audience reach metrics. The outcomes of this activity include improved knowledge and skills among Pokdarwis members in independently managing digital promotions, the establishment of more professional and active social media accounts, an increase in published promotional content, and enhanced digital visibility for the Nagari Sisawah tourism destination. In the long term, this initiative is expected to increase tourist numbers, strengthen the destination's image, and generate positive economic impacts for the local community through sustainable, community-based tourism development. Keywords: Digital marketing, Pokdarwis, tourism promotion, Nagari Sisawah, tourist visits